THE THEORETICAL BASIS OF STATE REGULATION OF GRAIN MARKET IN UKRAINE - M.V., Sikalo (Pressing Problems of Public Administration, 2016)
The theoretical basics for state regulation of the grain market in Ukraine in modern conditions have been considered; factors of further improvement of state regulation of the grain market of Ukraine have been identified.